Large-scale atmospheric forcing influencing the long-term variability of Mediterranean heat and freshwater budgets: climatic indices - Criado-Aldeanueva, Francisco; Soto-Navarro, Francisco Javier; García-Lafuente, Jesús (American Meteorological Society, 2013)
Interannual to interdecadal precipitation P, evaporation E, freshwater budget (E − P), and air–sea net heat flux Q have been correlated with the North Atlantic Oscillation (NAO), eastern Atlantic (EA), eastern Atlantic–western Russia (EA-WR), and Mediterranean Oscillation (MO) climatic indices to explore the influence of atmospheric forcing in the Mediterranean freshwater and heat budget variability. The effect of the MO pattern has similarities with that of the NAO, but MO influence is more intense. On an annual basis, the MO index gives the highest correlation with all the variables considered, and during its negative phase, it exerts a stronger influence than the NAO and is associated with higher P and, especially, enhanced evaporative losses in the Levantine subbasin. The EA pattern does not significantly affect P in the Mediterranean, but a high correlation is found for E and Q from 1979. The EA-WR mode plays a significant role in annual net heat flux since variations in its sign have the potential to induce seesaw variations in the heat budgets of the eastern and western subbasins, as previously found by Josey et al., for wintertime.
El copyritgh de este artículo pertenece a la editorial, American Meteorological Society.
Keywords: Mediterráneo - Clima - Observaciones; Temperatura - Mediterráneo; Circulación oceánica - Mediterráneo; Mediterranean Sea; Heat budget/fluxes; Indices; Water Budget; Decadal variability; Interannual variability